(untitled) (Homoeopathy for All, 2025)
Orthopedic conditions is an umbrella term encompassing osteoporosis, joint degeneration, fractures and related complications, which often stem from imbalances in structural and systemic integrity. Usually, these imbalances are conquered by supplementation of minerals that are essential for bone density and overall musculoskeletal health. Decreased bone mineral density is directly correlated with an increased risk of fractures, osteoporosis, etc. Osteoporotic bones exhibit lower mineral content and altered properties, making them more susceptible to breaks under stress. The use of minerals such as calcium, magnesium, phosphorous and others in the form of supplementation has been well-established in the field of modern medicine especially for such conditions.